Educational management in improving the quality of teachers in senior high schools - Dacholfany, Muhammad Ihsan; Suseno, Nyoto; Syofyan, Harlinda; Fadli, Muhammad Rijal (Institute of Advanced Engineering and Science, 2024)
Teachers play a crucial role in improving the quality of education, an essential aspect of national education development, which applies universally in various cultures and countries. As national education standards and needs increase, educational development becomes a necessity. This study seeks to investigate the enhancement of teacher quality dimensions to elevate national education standards, employing a case study approach with mixed methods. The sampling involved random selection from five senior high schools in Lampung, comprising 190 students and 10 teachers. Data collection was carried out through questionnaires, interviews, and document analysis. The analysis of questionnaire data utilized structural equation modeling (SEM) through Lisrel 8.50 assistance. The qualitative phase encompassed data reduction, presentation, conclusion drawing, and verification. Results indicate that the model fits well with a Satorra-Bentler scaled Chi-square value of 189.190, a p-value coefficient of 0.070 (>0.05), root mean square error of approximation (RMSEA) of 0.030 (<0.080), and comparative fit index (CFI)≥0.90, suggesting its acceptability. The assessment of teachers’ professional management in enhancing education quality focuses on preparation, implementation, and evaluation, offering significant potential for improving senior high school teachers’ quality.